Insulation material and method for manufacturing insulation material

By inducing dehydration and condensation reactions in a mixture of sodium silicate, alumina cement, and charcoal, the insulation material achieves high non-combustibility and stable manufacturing, addressing the inadequacies of conventional insulation materials.

JP7626474B2Active Publication Date: 2025-02-04EACH DREAM CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022541103
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-08-03
Filing Date
2020-09-18
Publication Date
2025-02-04
Estimated Expiration
2040-09-18

AI Technical Summary

Technical Problem

Conventional insulation materials are not sufficiently non-combustible, and materials like shells, which are natural products, have quality variations and storage challenges.

Method used

A method of producing insulation material by heating a mixture of sodium silicate, alumina cement, and charcoal to induce dehydration and condensation reactions, resulting in a highly non-combustible material.

Benefits of technology

The produced insulation material exhibits high non-combustibility, stable manufacturing, and improved thermal insulation properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007626474000002
    Figure 0007626474000002
  • Figure 0007626474000003
    Figure 0007626474000003
  • Figure 0007626474000004
    Figure 0007626474000004
Patent Text Reader

Abstract

This thermal insulation material contains a dehydration condensation reaction product of sodium silicate, an alumina cement and rice hull charcoal. It is preferable that this thermal insulation material additionally contains one or mor substances that are selected from the group consisting of silica-based hollow balloons, silicate minerals and diatomite. This thermal insulation material has, for example, a board shape. This method for producing a thermal insulation material causes a dehydration condensation reaction of sodium silicate by heating a starting material that contains sodium silicate, an alumina cement and rice hull charcoal.
Need to check novelty before this filing date? Find Prior Art

Description

CROSS-REFERENCE TO RELATED APPLICATIONS

[0001] This international application claims priority based on Japanese Patent Application No. 2020-131657, filed with the Japan Patent Office on August 3, 2020, the entire contents of which are incorporated herein by reference. [Technical field]

[0002] The present disclosure relates to insulation materials and methods of making insulation materials. [Background technology]

[0003] Conventionally, a heat insulating material made of foamed plastic is known. A heat insulating material made of foamed plastic is disclosed in Patent Document 1. Also, a heat insulating material containing rice husk is known. A heat insulating material containing rice husk is disclosed in Patent Document 2. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2010-121727 A [Patent Document 2] JP 2004-169547 A Summary of the Invention [Problem to be solved by the invention]

[0005] Conventional insulating materials do not have sufficient non-combustibility. In one aspect of the present disclosure, it is preferable to provide an insulating material having high non-combustibility and a method for manufacturing the insulating material. [Means for solving the problem]

[0006] One aspect of the present disclosure is an insulating material comprising a dehydration condensation reaction product of sodium silicate, alumina cement, and charcoal. The insulating material according to one aspect of the present disclosure has high non-combustibility.

[0007] Another aspect of the present disclosure is a method for producing a thermal insulation material, which comprises heating a raw material containing sodium silicate, alumina cement, and charcoal to cause a dehydration condensation reaction in sodium silicate. According to the method for producing a thermal insulation material which is another aspect of the present disclosure, a thermal insulation material having high non-combustibility can be produced. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is an explanatory diagram showing a method for evaluating a thermal insulation material. [Diagram 2] FIG. 2 is a perspective view illustrating a configuration of a first test piece. [Diagram 3] FIG. 2 is a perspective view illustrating a configuration of a second test piece. [Figure 4] FIG. 4 is a cross-sectional view taken along line IV-IV in FIG. [Explanation of symbols]

[0009] Reference Signs List 1...test specimen, 3...front surface, 5...reverse surface, 6...burner, 7...data logger, 11...first insulation material, 13...one side, 15...coating layer, 17...first test piece, 19...second insulation material, 21...coating layer, 23...second test piece DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Exemplary embodiments of the present disclosure will now be described with reference to the drawings.

[0011] 1. Composition of insulation material The heat insulating material contains (a) a dehydration condensation reaction product of sodium silicate, (b) alumina cement, and (c) charcoal. The dehydration condensation reaction product of sodium silicate, which is component (a), is a product produced by a dehydration condensation reaction of sodium silicate. Component (a) is, for example, a compound having a skeleton in which siloxane bonds are linked together. Component (a) includes, for example, siloxane. Component (c) charcoal is produced by carbonizing rice husks or wood chips through steaming.

[0012] The heat insulating material preferably contains 40 to 100 parts by mass of the component (b) per 100 parts by mass of the component (a). When the amount of the component (b) in the heat insulating material is within this range, the heat resistance of the heat insulating material is even higher.

[0013] The heat insulating material preferably contains 30 to 80 parts by mass of the (c) component per 100 parts by mass of the (a) component. When the amount of the (c) component in the heat insulating material is within this range, the heat insulating property of the heat insulating material is further improved.

[0014] The insulating material further includes, for example, one or more selected from the group consisting of silica-based hollow balloons, silicate minerals, and diatomaceous earth. When the insulating material includes silica-based hollow balloons, the insulating material has higher non-combustibility. When the insulating material includes silicate minerals, the insulating material has higher adhesive strength between the insulating material and other members. When the insulating material includes diatomaceous earth, the insulating material has higher durability.

[0015] The heat insulating material preferably contains 3 to 15 parts by mass of silica-based hollow balloons per 100 parts by mass of component (a). When the amount of silica-based hollow balloons is within this range, the heat insulating property of the heat insulating material is further improved.

[0016] The heat insulating material preferably contains 1 to 10 parts by mass of silicate mineral per 100 parts by mass of component (a). When the amount of silicate mineral is within this range, the heat insulating material has higher non-combustibility.

[0017] The heat insulating material preferably contains 3 to 20 parts by mass of diatomaceous earth per 100 parts by mass of component (a). When the amount of diatomaceous earth is within this range, the heat insulating material has higher non-flammability.

[0018] The shape of the heat insulating material is not particularly limited. The shape of the heat insulating material is, for example, a board shape. The heat insulating material can be used, for example, in buildings, heavy machinery, vehicles, etc. Examples of buildings include refrigerated warehouses, etc. When using the heat insulating material in heavy machinery or vehicles, for example, the heat insulating material can be placed around a heat generating member. Examples of heat generating members include an internal combustion engine, etc.

[0019] 2. Manufacturing method of insulation material In the method for producing a thermal insulation material of the present disclosure, a raw material containing sodium silicate, alumina cement, and charcoal is heated to cause a dehydration condensation reaction of sodium silicate. The produced thermal insulation material contains components (a), (b), and (c). 100 parts by mass of sodium silicate becomes 60 parts by mass of component (a) as a result of the dehydration condensation reaction.

[0020] The raw material preferably contains 40 to 60 parts by mass of alumina cement per 100 parts by mass of sodium silicate. When the amount of alumina cement is within this range, the non-combustibility of the heat insulating material is further improved.

[0021] The raw material preferably contains 20 to 50 parts by mass of charcoal per 100 parts by mass of sodium silicate. When the amount of charcoal blended is within this range, the insulating material has higher heat insulating properties.

[0022] The raw material further includes, for example, one or more selected from the group consisting of silica-based hollow balloons, silicate minerals, and diatomaceous earth. When the raw material includes silica-based hollow balloons, the insulating material has higher non-combustibility. When the raw material includes silicate minerals, the insulating material has higher adhesive strength between the insulating material and other members. When the raw material includes diatomaceous earth, the insulating material has higher durability.

[0023] The raw material preferably contains 1 to 10 parts by mass of silica-based hollow balloons per 100 parts by mass of sodium silicate. When the amount of silica-based hollow balloons is within this range, the insulating material has higher heat insulating properties.

[0024] The raw material preferably contains 1 to 10 parts by mass of silicate mineral per 100 parts by mass of sodium silicate. When the amount of silicate mineral is within this range, the non-combustibility of the heat insulating material is further improved.

[0025] The raw material preferably contains 3 to 20 parts by mass of diatomaceous earth per 100 parts by mass of sodium silicate. When the amount of diatomaceous earth is within this range, the durability of the heat insulating material is further increased.

[0026] In the method for producing a thermal insulation material according to the present disclosure, for example, a raw material having fluidity is poured into a mold, thereby producing a thermal insulation material having a shape corresponding to the mold. The shape of the thermal insulation material is, for example, a board shape.

[0027] 3. Effects of insulation materials (3-1) The insulating material disclosed herein is highly non-flammable.

[0028] (3-2) The rice husks used in conventional insulation materials are natural products, and therefore have a large variation in quality. In addition, rice husks are only produced in certain seasons. In addition, it is difficult to store rice husks for long periods of time. Compared to rice husks, charcoal is less susceptible to the above problems. Therefore, the insulation material of the present disclosure can be manufactured stably.

[0029] 4. Example 1 (4-1) Manufacturing of insulation materials The following ingredients were mixed together to obtain a liquid raw material:

[0030] Sodium silicate JIS No. 3: 100 parts by weight Silica-based hollow balloons: 10 parts by mass Silicate mineral (wollastonite): 5 parts by weight Diatomaceous earth: 10 parts by weight Special cement: 70 parts by weight Smoky charcoal: 50 parts by mass Water: 30 parts by mass The special cement corresponds to alumina cement. Next, the liquid raw material was poured into a mold and heated at 70°C for three hours to obtain a solid insulation material. The insulation material was in the form of a board. When heated, the sodium silicate contained in the raw material became a dehydration condensation reaction product.

[0031] (4-2) Evaluation of insulation materials A plate-shaped specimen 1 was prepared from the produced heat insulating material. The size of specimen 1 was 300 mm in length, 300 mm in width, and 16 mm in thickness.

[0032] As shown in Fig. 1, a point on one surface 3 of the test piece 1 was set as a first measurement point P1. A point on the back surface 5 of the test piece 1 was set as a second measurement point P2. The back surface 5 is the surface opposite to the front surface 3. A straight line passing through the first measurement point P1 and the second measurement point P2 is parallel to the thickness direction of the test piece 1.

[0033] The first measurement point P1 was continuously heated using a burner 6. The burner 6 was a power torch RZ-840 manufactured by Shinfuji Burner Co., Ltd. The room temperature was 23°C.

[0034] During the period in which the first measurement point P1 was being heated, the temperature of the first measurement point P1 and the temperature of the second measurement point P2 were continuously measured using a thermocouple. The measured temperatures were recorded by a data logger 7. The measurement results are shown in Table 1. The elapsed time in Table 1 refers to the time elapsed from the point in time when heating of the first measurement point P1 was started.

[0035] [Table 1] As shown in Table 1, even if the temperature at the first measurement point P1 rose, the temperature at the second measurement point P2 did not rise easily. Furthermore, even after 10 minutes had elapsed, the test piece 1 did not catch fire. This evaluation result indicates that the insulation material has high thermal insulation and non-combustibility.

[0036] 5. Example 2 (5-1) Manufacturing of insulation materials The following ingredients were mixed together to obtain a liquid raw material:

[0037] Sodium silicate JIS No. 3: 100 parts by weight Silica-based hollow balloons: 4 parts by mass Silicate mineral (wollastonite): 2 parts by weight Diatomaceous earth: 8 parts by weight Special cement: 60 parts by weight Smoky charcoal: 40 parts by mass Water: 40 parts by mass The special cement corresponds to alumina cement. Next, the liquid raw material was poured into the first mold and heated at 70°C for 3 hours to obtain the first insulation material. The first insulation material had a solid board shape. The size of the first insulation material was 99 mm long, 99 mm wide, and 15 mm thick. When heated, the sodium silicate contained in the raw material became a dehydration condensation reaction product. Next, the first insulation material was removed from the first mold.

[0038] The liquid raw material was poured into a second mold and heated at 70°C for 3 hours to obtain a second insulating material. The shape of the second insulating material was a solid cylinder. The diameter of the second insulating material was 44 mm. The height of the second insulating material was 50 mm. When heated, the sodium silicate contained in the raw material became a dehydration condensation reaction product. Next, the second insulating material was removed from the second mold.

[0039] (5-2) Preparation of test specimens The following components were mixed to obtain a liquid coating agent.

[0040] Sodium silicate JIS No. 3: 74.0 parts by mass Shirasu balloon: 7.4 parts by weight Silicate mineral (wollastonite): 7.4 parts by mass Alumina cement: 11.2 parts by mass As shown in FIG. 2, a coating layer 15 was formed on one side 13 of a first insulating material 11. The method for forming the coating layer 15 was to apply a coating agent to one side 13 and heat it at 100° C. for 3 hours. The thickness of the coating layer 15 was 0.5 mm. The first insulating material 11 provided with the coating layer 15 was used as a first test piece 17.

[0041] As shown in Figures 3 and 4, a coating layer 21 was formed on the entire surface of the second insulating material 19. The method for forming the coating layer 21 was to apply a coating agent to the entire surface of the second insulating material 19 and heat it at 100°C for 3 hours. The thickness of the coating layer 21 was 0.5 mm. The second insulating material 19 provided with the coating layer 21 was used as a second test piece 23.

[0042] (5-3) Evaluation of heat generation The first test piece 17 was subjected to a heat generation test in accordance with ISO-5660. In the heat generation test, the first test piece 17 was heated for 20 minutes. The radiation intensity was 50 kW / m 2 The surface to which radiant heating was applied was 13 on one side.

[0043] Total calorific value is 0.2MJ / m 2 The maximum heat release rate was 1.88kW / m 2 , which was very low. After the heat generation test, no deformation occurred in the first test piece 17. The first test piece 17 did not ignite. The results of the heat generation test show that the first test piece 17 has high non-combustibility.

[0044] (5-4) Evaluation of non-flammability The second test pieces 23 were subjected to a non-combustibility test in accordance with ISO-1182. The test method was as follows. A cylindrical electric furnace was prepared. Three second test pieces 23 were used in the test. The masses of the second test pieces 23 before the test were 63.9 g, 64.5 g, and 73.6 g, respectively.

[0045] The temperature inside the electric furnace was adjusted to 750±5°C. After the temperature inside the furnace was adjusted, the power consumption of the electric furnace was kept constant. After the temperature inside the furnace was adjusted, the second test piece 23 was inserted into the furnace. After the second test piece 23 was inserted, the temperature inside the furnace and the surface temperature of the second test piece 23 were continuously measured. In addition, the mass of the second test piece 23 was measured before and after the test. In addition, the shape of the second test piece 23 was observed before and after the test. The test was continued until the temperature inside the furnace reached the final equilibrium temperature. The final equilibrium temperature is the temperature inside the furnace when the temperature inside the furnace became stable within a range of ±2°C for 10 minutes.

[0046] The increased furnace temperature on the surface of the second test piece 23 was 5.0°C, 1.3°C, and -0.5°C. The increased furnace temperature is the maximum furnace temperature minus the final equilibrium temperature. The maximum furnace temperature is the maximum furnace temperature during the period from the insertion of the second test piece 23 to the end of the test. The mass reduction rates WR of the second test piece 23 were 13.1%, 14.2%, and 13.0%. The mass reduction rate WR is a value expressed by the following formula (1).

[0047] Formula (1) WR=((W1-W2) / W1)×100 In formula (1), W1 is the mass of the second test piece 23 before the test, and W2 is the mass of the second test piece 23 after the test.

[0048] The furnace temperature rise on the surface of the second test piece 23 was smaller than 20°C, which is the standard in ISO-1182. The mass reduction rate WR was smaller than 30%, which is the standard in ISO-1182. The shape of the second test piece 23 after the test did not change significantly compared to the shape of the second test piece 23 before the test. The results of the non-combustibility test show that the second test piece 23 has high non-combustibility.

[0049] 6. Other embodiments Although the embodiments of the present disclosure have been described above, the present disclosure is not limited to the above-described embodiments and can be implemented in various modified forms.

[0050] (6-1) Multiple functions possessed by one component in the above embodiments may be realized by multiple components, or one function possessed by one component may be realized by multiple components. Also, multiple functions possessed by multiple components may be realized by one component, or one function realized by multiple components may be realized by one component. Also, part of the configuration of the above embodiments may be omitted. Also, at least part of the configuration of the above embodiments may be added to or substituted for the configuration of another of the above embodiments.

[0051] (6-2) In addition to the above-described insulating material, the present disclosure can be realized in various forms, such as a system that includes the insulating material as a component.

Claims

1. A dehydration condensation reaction product of sodium silicate; Alumina cement, Smoked charcoal and Silicate minerals; An insulating material comprising: A heat insulating material comprising the silicate mineral in an amount of 1 part by mass or more and 10 parts by mass or less per 100 parts by mass of the dehydration condensation reaction product of sodium silicate.

2. The thermal insulation material according to claim 1, An insulation material in the form of a board.

3. A method for producing a thermal insulation material, comprising the steps of: A raw material containing sodium silicate, alumina cement, charcoal, and a silicate mineral is heated to cause a dehydration condensation reaction of sodium silicate, The raw material contains 1 part by mass or more and 10 parts by mass or less of the silicate mineral per 100 parts by mass of the sodium silicate.

4. A method for producing the heat insulating material according to claim 3, A method for producing an insulating material, comprising pouring the raw material into a mold to produce the insulating material having a board-like form.

Citation Information

Patent Citations

  • Insulating material for smelting or casting metal

    JP1979026232A

  • Manufacture of water-repellant calcium silicate formed body

    JP1986251554A

  • Refractory heat insulating board

    JP1987246880A

  • Heat insulation material

    JP1994099272A

  • Thermal insulation material for construction, wooden building using the thermal insulation material for construction, and its construction method

    JP2004169547A